2020
DOI: 10.1101/2020.01.21.914044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host and infectivity prediction of Wuhan 2019 novel coronavirus using deep learning algorithm

Abstract: The recent outbreak of pneumonia in Wuhan, China caused by the 2019 Novel Coronavirus (2019-nCoV) emphasizes the importance of detecting novel viruses and predicting their risks of infecting people. In this report, we introduced the VHP (Virus Host Prediction) to predict the potential hosts of viruses using deep learning algorithm. Our prediction suggests that 2019-nCoV has close infectivity with other human coronaviruses, especially the severe acute respiratory syndrome coronavirus (SARS-CoV), Bat SARS-like C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
108
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 18 publications
0
108
0
Order By: Relevance
“…Zhu and colleagues used deep learning algorithms to analyze the gene sequences of novel coronaviruses and other coronaviruses to predict potential viral hosts. Their results indicated that bats and minks may be the two potential hosts of the novel coronavirus, while minks may be the intermediate hosts of the virus [5]. The novel coronavirus showed a similar pattern of infection to other coronaviruses in humans, particularly severe acute respiratory syndrome coronavirus (SARS-nCoV), Bat SARS-like CoV, and Middle East respiratory syndrome coronavirus (MERS-nCoV).…”
Section: Introductionmentioning
confidence: 99%
“…Zhu and colleagues used deep learning algorithms to analyze the gene sequences of novel coronaviruses and other coronaviruses to predict potential viral hosts. Their results indicated that bats and minks may be the two potential hosts of the novel coronavirus, while minks may be the intermediate hosts of the virus [5]. The novel coronavirus showed a similar pattern of infection to other coronaviruses in humans, particularly severe acute respiratory syndrome coronavirus (SARS-nCoV), Bat SARS-like CoV, and Middle East respiratory syndrome coronavirus (MERS-nCoV).…”
Section: Introductionmentioning
confidence: 99%
“…: MN996532), with 96.2% nucleotide homology in the whole genome Zhou et al, 2020). Other groups suggest that pangolin, mink, snake, turtle may be potential intermediate hosts for the virus (Association, 2020;Guo et al, 2020;Ji et al, 2020;Lam et al, 2020;Li et al, 2020;Liu et al, 2020a;Liu et al, 2020b;Xiao et al, 2020;Zhang et al, 2020a;Zhang et al, 2020b), which still need more evidence to be confirmed.…”
Section: To the Editormentioning
confidence: 99%
“…They considered that snake was a most probable wildlife animal reservoir, but the conclusion was controversial. Guo et al introduced VHP (Virus Host Prediction) to predict the potential hosts of viruses by deep learning algorithm and predicted that bat coronaviruses were assigned with more similar infectivity patterns with SARS-CoV-2 [14] . The results illustrated that bat and mink might be two candidate reservoirs of SARS-CoV-2.…”
Section: Potential Hostsmentioning
confidence: 99%